1982
DOI: 10.1007/bf01952658
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic studies of efferent nerves from the celiac ganglion in the cat

Abstract: Summary. Postganglionic sympathetic fibers originating in the celiac ganglion can be traced by autoradiography to the stomach, spleen, liver and pancreas.Autoradiography is a method widely used for tracing pathways in the CNS but its use in the peripheral nervous system has been more limited 1-5. Recently Kelts 6 has reported using this method to trace efferent fibers from the left celiac ganglion of cats to the contralateral celiac ganglion, satellite ganglia between the 2 celiac ganglia, and the adrenal glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Anterograde tracing techniques have also been employed to examine the origin of sympathetic fibers that innervate the GI tract. Dickhaus and Connors (57) reported that radiolabeled leucine injected into the celiac ganglia of cats could be traced autoradiographically to the stomach. Spinal cord input to the stellate, celiac, and superior mesenteric ganglia was found to originate in cell bodies in the intermediolat-era1 cell columns of spinal cord segments SMALL INTESTINE.…”
Section: Sympathetic Neural Pathwaysmentioning
confidence: 99%
“…Anterograde tracing techniques have also been employed to examine the origin of sympathetic fibers that innervate the GI tract. Dickhaus and Connors (57) reported that radiolabeled leucine injected into the celiac ganglia of cats could be traced autoradiographically to the stomach. Spinal cord input to the stellate, celiac, and superior mesenteric ganglia was found to originate in cell bodies in the intermediolat-era1 cell columns of spinal cord segments SMALL INTESTINE.…”
Section: Sympathetic Neural Pathwaysmentioning
confidence: 99%